Partnerships for scaling Gender and Nutrition Sensitive Climate-Smart Agriculture: Science for Impact 2015-2021 - World Agroforestry Centre (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
P4S is a cross-institution program led by World Agroforestry (ICRAF) and the International Center for Tropical Agriculture (CIAT) in collaboration with other CGIAR centers, development, government and private sector partners. P4S supports scaling up and out of CSA by working in close collaboration with partners to generate credible, relevant and legitimate evidence.